HUBUNGAN HIPERGLIKEMIA DENGAN KADAR GLYCERALDEHYDE-3-PHOSPHATE DEHYDROGENASE (GAPDH) PADA PENDERITA DIABETES MELLITUS TIPE 2 - Yessi Alza (Sistem Informasi, 2013)
Diabetes mellitus (DM) is a group of metabolic disease with characteristic hyperglycemia. Glycosylated hemoglobin (HbA1C) > 7% indicated uncontrolled DM. Hyperglycemia causes excessive production of free radicals that trigger oxidative stress. Oxidative stress is caused primarily by superoxide anion mitochondrial DNA would undermine the core so that it will activate PARP. PARP is activated would inhibit the activity of GAPDH in the glycolytic pathway. Inhibited glycolysis pathway will lead to reactions that formed splinter polyol pathway, increased PKC and increased hexosamine pathway.The research design was cross sectional comparative study, conducted in Internal Medicine Department of Dr. M.Djamil Hospital in Padang, Biomedical Laboratory of Medical College, Chemical Laboratory of College of Mathematics and Physical Sciences Andalas University. The total number of samples are 70, divided into two group, consist of 35 people cases and 35 people controlled. ELISA method was used for examination of GAPDH activity.The research results are activity GAPDH in patients with T2DM in lower that the non DM, but not statistically significant. Regression correlation analysis for relationship between fasting blood sugar with the activity of GAPDH denoted weak correlation, r = 0,179 (p=0,139), and the relationship of blood glucose levels 2 hours post prandial with GAPDH levels in patients with T2DM obtained a weak correlation with r values = 0.039 (p = 0.749).The research conclusion are there is no significant difference between GAPDH activity in patients with T2DM and non DM, there is a weak relationship between hyperglycemia with GAPDH activity.